Mexico : The Strategy to Achieve Sustained Economic Growth - Loser, Claudio (Occasional Papers; Occasional Paper, 1992)
This paper explores the reasons behind the recent transformation and upturn of the Mexican economy. the changes are the result of the authorities' determination to stick with a difficult reform program since the early 1980s, supported by multilateral financial institutions, creditor countries, and commercial banks.